ПРОФІЛЬ ЕКСПРЕСІЇ CD150 У КЛІТИНАХ КІСТКОВОГО МОЗКУ ХВОРИХ НА ГОСТРИЙ МІЄЛОЇДНИЙ ЛЕЙКОЗ - Shlapatska, L.; Gordiienko, I.; Polishchuk, A.; Gluzman, D. (PH Akademperiodyka, 2023)
Background: Acute myeloid leukemia (AML) is a highly heterogeneous disease accompanied by the arrest of myeloid cell lineage differentiation due to accumulation of genetic abnormalities and clonal proliferation of myeloid blasts. Finding the differentially expressed molecules and studying their function within AML subgroups may help to improve diagnosis and prognosis with the aim of developing selected therapies for AML subsets. The aim of this study was to reveal the profile of CD150 cell surface expression on bone marrow (BM) cells of AML patients. Materials and Methods: The study was performed on samples of BM aspirates from 55 patients with primarily diagnosed AML. Flow cytometry analysis was applied for the evaluation of immunophenotype profile and CD150 cell surface expression on BM cells from AML patients. Results: Four AML subtypes (M1, M2, M3 and M5) were identified. The CD150 expression was found in 14 (25.5%) cases predominantly of AML M3 subtype. CD150 expression was detected on 43.2–83.8% of leukemia cells in AML M3. The frequency of CD150 positive cases of non-M3 AML subtypes was low: all AML M1 cases were CD150-negative, while only 1 (10.0%) of 10 patients with AML M2 and 6 (19.4%) of 31 patients with AML M5 were CD150 positive. The median percentage of CD150 positive leukemia cells and the index of mean fluorescence intensity in AML M3 cases were significantly higher than in non-M3 AML cases (p < 0.05). The CD150 expression was significantly associated with CD11c, CD11b, CD14, CD34, CD36, CD56 and HLA-DR negative expression and CD33, CD38, CD117 positive expression among the examined cohort of patients with AML M3. Conclusions: High level of CD150 expression is a unique feature of AML M3 subtype and may serve as additional phenotype marker for the identification of blast cells with impaired maturation at the promyelocyte stage and the development of AML M3. At the same time, the revealed negative association of CD150 expression with poor prognostic factor CD56 in AML M3 subtype also allows us to suggest potential prognostic value of CD150 examination in AML patients.